Involvement of the lncRNA AFAP1‐AS1/microRNA‐195/E2F3 axis in proliferation and migration of enteric neural crest stem cells of Hirschsprung's disease. Issue 11 (7th October 2020) - Pan, Weikang; Wu, Ali; Yu, Hui; Yu, Qiang; Zheng, Baijun; Yang, Weili; Tian, Donghao; Li, Peng; Gao, Ya
Abstract : New Findings: What is the central question of this study? Long non‐coding RNAs (lncRNAs) are widely involved in the progression of Hirschsprung's disease (HSCR), but the role of actin filament associated protein 1 antisense RNA1 ( AFAP1‐AS1 ), an lncRNA, in HSCR has not been explored before. What is the main finding and its importance? Downregulation of AFAP1‐AS1 blocks enteric neural crest stem cell proliferation, differentiation, migration and invasion and promotes the occurrence of HSCR via the miR‐195/E2F3 axis, indicating that AFAP1‐AS might be a potential biomarker for HSCR patients. Abstract: Long non‐coding RNAs (lncRNAs) are involved in several human disorders. Nevertheless, it remains unclear whether they are implicated in the phenotypes of enteric neural crest stem cells (ENCSCs) in Hirschsprung's disease (HSCR). Therefore, we designed this study to explore the pathogenicity of AFAP1‐AS1 for HSCR. Microarray analysis and bioinformatic tools were used to screen out the differentially lncRNAs and microRNAs (miRNAs) in patients with HSCR. Small interference RNA transfection was applied to carry out functional experiments in ENCSCs. Cellular activities were detected by cell counting kit‐8, 5‐ethynyl‐2′‐deoxyuridine, Transwell assays and flow cytometry. Finally, rescue experiments were performed to examine the cofunction of AFAP1‐AS1 and miR‐195 and of miR‐195 and E2F transcription factor 3 ( E2F3 ). AFAP1‐AS1 was reduced in HSCR patients. Meanwhile, knockdown of AFAP1‐AS1 reduced the cell migratory and proliferative capacities and facilitated cell apoptosis along with G0/G1 phase arrest. E2F3 was diminished when miR‐195 was upregulated, and AFAP1‐AS1 inhibition reduced its ability to bind to miR‐195 . Altogether, AFAP1‐AS1 silencing acts as an endogenous RNA by interacting with miR‐195 to alter E2F3 expression, thus conferring repressive effects on ENCSC activity and promoting HSCR progression. Abstract :